As mutações da escola média na Argentina no marco da reconfiguração de um mundo globalizado - Tiramonti, María Guillermina (2008)
In this text, the author analyzes the reorganization of educational systems and the processes that have affected it along the important social and cultural changes of the latest years. She also introduces the idea of a fragmentation of the educational system, establishing differences between this new concept and the traditional concept of educational breakup, and explaining this conceptualization with theoretical bases. She also approaches the changes in institutional structures, generated by modernity (family, the State and schools) as well as their impact on the constitution of subjectivities through the characterization of asynchrony in the individualization of students from different socio-cultural backgrounds. The author finally identifies prescriptions which are present-time demands and must be faced by schools in terms of inclusion, restraint and fulfillment.